Specifics of Research and Development Project Management – Case Study of NANOBIO Project - Koucká, Kristýna; Košťálová, Jana; Munzarová, Simona; Záhorská, Alexandra (European Publisher, 2021)
In the current strong pressure of the competitive environment, companies are forced to monitor scientific and technical changes that could affect the business areas in which they operate. There is a dynamic increase in innovation, which leads to higher demands on investment in research and development due to a more flexible response to change. The area of research and development is very important for fulfilling the company's strategy and research and development is becoming increasingly important for maintaining competitiveness and in terms of sustainability. Changes in research and development are implemented in the form of projects, which are specific to a high degree of uncertainty and risk, which limits the possibilities of using traditional waterfall project management procedures. Research and development projects take many forms depending on the nature of the research, the focus of the innovation and the field of implementation. The article focuses on the specifics of research and development projects, assessment of the possibilities of using methods of waterfall and agile project management, or their combinations and evaluation of how to manage the basic parameters of research and development projects. Subsequently, in the form of a case study, it assesses the form of application of project management methods and tools to a specific research and development project. In general, the article provides recommendations for the management of research and development projects and the proposal of appropriate procedures for unplanned activities in the project with the help of combinations of waterfall project management and agile project management.
Specifika řízení projektů výzkum a vývoje - case study projektu NANOBIO
Keywords: agile project management; NANOBIO; project management; research and development project management; waterfall project management; agilní projektové řízení; NANOBIO; projektový management; řízení projektů výzkumu a vývoje; vodopádové projektové řízení